Cystic intra-abdominal masses in children - Luisa Ferrero; Riccardo Guanà; Giulia Carbonaro; Maria Grazia Cortese; Luca Lonati; Elisabetta Teruzzi; Jurgen Schleef (MDPI AG, 2017)
Benign intra-abdominal cystic masses in infancy are fairly uncommon and their etiopathogenesis, histology and clinical presentation differ significantly. Our aim is to report our experience in their treatment in order to discuss the best diagnostic and treatment modality. The medical records of 5 children (2M, 3F) with cystic intraabdominal masses referred to our hospital between November 2012 and September 2016, were retrospectively reviewed. All patients underwent open surgery and subsequent histopathologic analysis. Different clinical presentations, localizations of the masses, diagnostic tools, surgical approaches, histological examinations and outcomes were reviewed. Patients mean age was 5.4 years (range: 8 months-9 years). Two patients presented recurrent abdominal pain and abdominal distension; 1 patient had a palpable mass discovered incidentally and 2 complained acute abdominal pain. Routine laboratory tests, tumor markers and abdominal ultrasound were immediately done in all patients. Three patients underwent MRI and 1 abdominal CT. At laparotomy 2 hepatic cysts, 2 mesenteric cyst and 1 retroperitoneal cyst were discovered. Histology reports described: 1 hepatobiliary cystadenoma, 1 benign hepatic hamartoma and 3 cystic lymphangiomas (1 retroperitoneal and 2 mesenteric). There were no major postoperative complications, deaths, or recurrences in our series (follow-up 3-24 months). Despite the rarity of these lesions, benign cystic abdominal masses in children are not so uncommon and should be considered as causes of acute abdominal pain. The differential diagnosis is not always possible preoperatively. In our series, radical excision of the lesions was possible in all cases, allowing reliable histological results and avoiding recurrences.